Voice treatment of school-aged children with vocal nodules with ABCLOVE rehabilitation - Yanrui Bian; Jingmiao Wang; Haizhong Zhang; Xiaoyan Yin; Yubo Zhang (Elsevier, 2024)
Background: This study was to explore the effectiveness of the ABCLOVE exercise on school-aged children with vocal nodules after the treatment of budesonide. Methods: Eighty-six school-aged children with vocal nodules were divided into control and ABCLOVE therapy groups. Subjective voice assessment and dysphonia severity index (DSI) assessment were performed before and after the 3-month of therapy. Results: A significant improvement was observed in the ABCLOVE therapy group as compared with the control group (p = 0.035). ABCLOVE therapy significantly reduced the hoarseness and roughness scores in school-aged children with vocal nodules. Additionally, a significant reduction in functional score, physical score, emotional score, and total pVHI score was observed in the ABCLOVE therapy group. Moreover, acoustic parameters including jitter (%) and shimmer (%) were significantly reduced, whereas MPT and DSI were increased in school-aged children with vocal nodules who received 3 months of ABCLOVE treatment. Conclusion: ABCLOVE therapy displayed effectiveness on school-aged children with vocal nodules after the treatment of budesonide.